Alkaloids isolated from the bark of Alseodaphne Peduncularis (Wall.Ex Nees) MEISN and the roots of Alseodaphne Corneri Kosterm - Siti Nor Fadzilah Mohamad (Tanjong Malim, 2014)
Alkaloids isolated from the bark of Alseodaphne Peduncularis (Wall.Ex Nees) MEISN and the roots of Alseodaphne Corneri Kosterm by Siti Nor Fadzilah Mohamad